Legal Analysis Of Vat Obligations Of Personal Personnel, Notary And Notary / PPAT - Satria , Friyan (Journal of Industrial Engineering & Management Research, 2021)
Every taxpayer in Indonesia who has had NPWP is required to carry out his right and obligation according to the prevailing regulations. An appointed Notary/PPAT has already had NPWP. Article 28 of UU KUP, Article 14 of UU PPh, and PER-17/PJ/2015 which regulates the calculation of PPh OP Notary/PPAT for gross circulation below Rp. 4.8 million can choose to organize bookkeeping or calculating norm, while a Notary/PPAT who has his earnings Rp.4.8 million or more has to organize bookkeeping. Regulation on the calculation of PPh of individuals for a Notary/PPAT who obtains earnings from professional service and business does not meet the principle of justice, either vertically or horizontally, because ideally the same earnings will have the same amount of tax, and the bigger the earnings, the more taxable which has to be paid. This type of research is a research that uses a normative approach and the nature of the research is a descriptive research. The secondary data in question is in the form of legal materials which are described as follows: Primary legal materials are used by researchers as strong basic legal materials as the main basis for conducting analysis. Some of the legal materials in question are the Law on General Provisions and Tax Procedures, Income Tax Law, Government Regulation Number 46 of 2013. Secondary legal materials in the form of legal materials related to primary legal materials that can assist researchers in analyzing and understanding primary legal materials. Tertiary legal materials are legal materials which are information related to research such as legal dictionaries, articles, news, and so on.